Pengembangan Layanan Inovatif Dengan Analisis Blue Ocean Strategy di KSPPS BMT NU Sejahtera Bumiayu - Humeriatunnisa, Asky; Salsabila, Mischel; Putri, Nindita Septiana; Shafrani, Yoiz Shofwa (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
The rise of digital transformation and increasing competition in the Islamic financial sector require microfinance institutions such as KSPPS BMT NU Sejahtera Bumiayu to implement innovative strategies to build competitive advantage. This study aims to analyze the development of innovative services through the Blue Ocean Strategy (BOS) framework, which focuses on value creation and the discovery of untapped market space. A descriptive qualitative method was employed, with data collected through in-depth interviews involving management and active customers. The findings indicate that based on external analysis (PEST and Five Forces) and internal evaluation, the institution holds strong potential to develop service strategies driven by innovation. The application of the ERRC Grid led to several strategic actions, including eliminating administrative fees, simplifying procedures, enhancing service quality and technology, and developing the digital application BMT Mobile. The study concludes that BOS is an effective strategic framework for expanding inclusive, community-based Islamic finance. The results contribute both theoretically and practically to the development of adaptive and competitive Islamic microfinance service models.